Grand Parent of Parenting Style and Incidence of Stunting Among Toddlers in Indonesia: A Literature Review - Ramadhani, Ayu Parahita; Susanto, Tantut; Rasni, Hanny; Kurdi, Fahruddin (Al-Hijrah Indonesia, 2023)
Toddlers with stunting have similar parenting styles, especially parenting style of grandpa and/or grandma. Grand parents have roled for fulfilling toddler nutrition. Parenting style of grand parents is important to facilitate of nutrition among toddlers during their growth and development. The aimed of this study was to determine the parenting style of grandpa and/or grandma and incidence of stunting among toddlers in Indonesia. The research method was used a literature review study. Article search was carried out by searching the database through Google Scholar, PubMed, and Sinta using predetermined keyword combinations, which were then analyzed using a four-stage prism flowchart to obtain 12 articles for review. The results of a review of 12 articles found that authoritative parenting, authoritarian parenting, and permissive parenting are parenting styles adopted by grandparents that can influence the incidence of toddler stunting in Indonesia. Parenting styles of grandparents with authoritative parenting can affect optimal nutritional status and the risk of stunting with toddlers is very low, while parenting styles of grandparents with authoritarian and permissive parenting can affect poor nutritional status and have a high risk of stunting with toddlers. The conclusion from this study is that the parenting style of grandpa and/or grandma influences the incidence of stunting in toddlers.